2018
DOI: 10.3390/ijms19092672
|View full text |Cite
|
Sign up to set email alerts
|

lncRNAs in Non-Malignant Tissue Have Prognostic Value in Colorectal Cancer

Abstract: Although colorectal cancer (CRC) is the third most frequent cause of cancer related death in Europe, clinically relevant biomarkers for therapy guidance and prognosis are insufficiently reliable. Long non-coding RNAs (lncRNAs) are RNAs over 200 nucleotides long that are not translated into proteins but can influence biological processes. There is emerging evidence for their involvement in solid cancer as oncogenes, tumour suppressors or regulators of cell proliferation and metastasis development. The goal of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Thiele et al have indicated that LINC-RoR was associated with the progression of CRC. 23 Moreover, Li et al have outlined that LINC RoR can influence the cell proliferation via p53. 24 Yang et al revealed that LINC-RoR promoted the resistance of radiotherapy for human CRC cells by targeting the p53/miR-145 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thiele et al have indicated that LINC-RoR was associated with the progression of CRC. 23 Moreover, Li et al have outlined that LINC RoR can influence the cell proliferation via p53. 24 Yang et al revealed that LINC-RoR promoted the resistance of radiotherapy for human CRC cells by targeting the p53/miR-145 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MIR155HG was found to be a marker of early stage cancer development [20]. MIR155HG gene is activated by MYB transcription factor and thus up-regulated, which in turn leaded to down-regulation of many tumor suppressor genes [21].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of oral cancer always performed by the dentists with visual examination and palpation of the oral mucosa (Shibahara, 2017). Saliva contains abundant RNA molecules (Fabryova & Celec, 2014; Li et al, 2006), which serve as potential diagnostic markers of cancer (Achour & Aguilo, 2018; Chen et al, 2018; Chi et al, 2018; Thiele et al, 2018; Yu et al, 2017). Moreover, saliva collection is a non-invasive method that can be used to detect risk-associated biomarkers for diseases, and is more acceptable to certain age groups—i.e., children and the elderly—than blood sampling (Liu & Duan, 2012; Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%